Effects of Glucocorticoids on Postoperative Neurocognitive Disorders in Adult Patients: A Systematic Review and Meta-Analysis - Xie, Xiaoyu; Gao, Rui; Chen, Hai; Zhang, Xueying; Cai, Xingwei; Zhang, Changteng; Liu, Changliang; Zhu, Tao; Chen, Chan (Frontiers in Aging Neuroscience, 2022)
Background: Postoperative neurocognitive disorders (PNDs) is common among surgical patients, however, the effect of glucocorticoids for preventing PNDs is not clear. This review aims to evaluate the effect of glucocorticoids on the incidence of PNDs in adult patients undergoing surgery. Methods: The databases of PubMed/Medline, Embase, the Cochrane Library, and Web of science were searched for all available randomized controlled trials (RCTs) from inception to Apr 30, 2022. RCTs comparing the effect of glucocorticoids with placebo on the incidence of PNDs in adult surgical patients (≥ 18 years old) were eligible. Subgroup analyses and meta-regressions were performed to evaluate sources of clinical heterogeneity. The level of certainty for main outcomes were assessed by the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. Results: Eleven trials with a total of 10703 patients were identified. Compared with the control group, glucocorticoids did not reduce the incidence of PNDs (RR: 0.84, 95% CI: 0.67 to 1.06, P = 0.13, GRADE = moderate). Secondary analyses for primary outcome did not change the result. In addition, the length of ICU stay was decreased in glucocorticoids group (RR: -13.58, 95% CI: -26.37 to -0.80, P = 0.04, GRADE = low). However, there were no significant differences between groups with regards to the incidence of postoperative infection (RR: 0.94, 95% CI: 0.84 to 1.06, P = 0.30, GRADE = moderate), blood glucose level (RR: 1.05, 95% CI: -0.09 to 2.19, P = 0.07, GRADE = low), duration of mechanical ventilation (RR: -2.44, 95% CI: -5.47 to 0.59, P = 0.14, GRADE = low), length of hospital stay (RR: -0.09, 95% CI: -0.27 to 0.09, P = 0.33, GRADE = moderate) and 30-day mortality (RR: 0.86, 95% CI: 0.70 to 1.06, P = 0.16, GRADE = moderate). Conclusions: This meta-analysis suggests that perioperative administration of glucocorticoids may not reduce the incidence of PNDs after surgery. The effect of glucocorticoids on decreased length of ICU stay needs further researches. Future high-quality trials using acknowledged criteria and validated diagnostic tools are needed to determine the influence of glucocorticoids on long-term PNDs. Systematic Review Registration: Identifier CRD42022302262.